A Multi-Agency Approach to Combating Transnational Crime and Money Laundering - Ferry Yuli Mulyani; Yusuf M. Said; Magister Hukum STIH IBLAM (Jurnal Indonesia Sosial Sains, 2026)
The rapid development of globalization, digital technology, and international financial systems has significantly increased the complexity of transnational crimes, particularly money laundering and human trafficking. Advances in fintech, cryptocurrencies, and cross-border digital transactions have enabled criminal organizations to conceal illicit financial flows more effectively, creating substantial challenges for traditional law enforcement systems. This study aims to analyze the urgency and effectiveness of a multi-agency approach in combating transnational crime and money laundering in Indonesia. The research employed a qualitative descriptive-analytical method through a literature study approach, utilizing primary and secondary data derived from regulations, official reports, academic journals, policy documents, and international publications related to anti-money laundering systems and transnational crime prevention. The findings reveal that conventional and sectoral law enforcement approaches are no longer sufficient to address modern transnational crimes due to fragmented institutional coordination, limited data integration, and technological disparities among agencies. The study demonstrates that collaboration among financial intelligence agencies, law enforcement institutions, financial authorities, international organizations, and private sector actors is essential in establishing an integrated and adaptive monitoring system. Furthermore, the involvement of financial institutions and digital service providers plays a strategic role in detecting suspicious transactions and preventing illegal financial flows. In conclusion, the multi-agency approach represents a crucial strategy for strengthening Indonesia’s anti-money laundering framework and enhancing national resilience against increasingly sophisticated transnational crimes.